Design of Jewelry from The Architecture Pattern of Lanna Gingerbread house - Jaisuda, Thanakit; Phanpraejit2 , Yongyuth; Podjanapimol3 , Pornpimol (DEC Journal : Art and Design, 2023)
This research had the objective to study integrated architectural pattern of Gingerbread House to design of jewelry that reflected architectural uniqueness of the gingerbread house, Phrae province and to assess the consumer’s satisfaction with the jewelry prototype. The data of Kum Wong Buri architectural pattern were collected to study and analyze the uniqueness of the pattern in 3 points as follows. 1) Characteristics and structure of the pattern 2) Arrangement of components of the pattern and 3) the influence and symbolic meaning appeared in the pattern. The data above were used in designing jewelry to produce into prototype and then assessing the satisfaction of consumers toward such jewelry prototype. The results of the research show a guideline for jewelry design. It presents the process of designing and developing jewelry using unique architectural motifs as inspiration for design. Research on creating 1 set of jewelry under the name Glory of Memories, such jewelry is the result of the overall satisfaction assessment at the highest level of satisfaction. It is a clear confirmation that unique architectural motifs can be used to design unique jewelry. This research leads to a design development approach related to contemporary design trends. Which talks about creating a unique story making identity search and bringing cultural capital as a selling point.